The relationship between highly visual social media and young people's mental health: A scoping review. (August 2020) - McCrory, Alanna; Best, Paul; Maddock, Alan
Abstract: Users of highly visual social media (HVSM), such as Snapchat and Instagram, share their messages through images, rather than relying on words. A significant proportion of people that use these platforms are adolescents. Previous research reveals mixed evidence regarding the impact of online social technologies on this age group's mental wellbeing, but it is uncertain whether the psychological effects of visual content alone differ from text-driven social media. This scoping review maps existing literature that has published evidence about highly visual social media, specifically its psychological impact on young people. Nine electronic databases and grey literature from 2010 until March 2019 were reviewed for articles describing any aspect of visual social media, young people and their mental health. The screening process retrieved 239 articles. With the application of eligibility criteria, this figure was reduced to 25 articles for analysis. Results indicate a paucity of data that exclusively examines HVSM. The predominance of literature relies on quantitative methods to achieve its objectives. Many findings are inconsistent and lack the richness that qualitative data may provide to explore the reasons for theses mixed findings.